Implementing the Handwashing Dance on Early Childhood Health Literacy: A Case Study at TK Siti Sulaechah 01 Semarang - Gladis Alfioni , Meysifa; Mukminin, Amirul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study explores the implementation of the Handwashing Dance as an innovative tool to promote early childhood health literacy at TK Siti Sulaechah 01 Semarang. Employing a qualitative research design, the research aimed to provide a comprehensive understanding of the effects of this method on children's knowledge and practices regarding hand hygiene. Data were collected through interviews, observations, and document analysis involving the principal, teachers, and parents of Group B2. The findings indicated that the Handwashing Dance significantly improved children’s cognitive, affective, and psychomotor skills related to handwashing. Specifically, children demonstrated better recall of handwashing steps, increased enthusiasm and participation in hygiene activities, and improved coordination in handwashing movements. Teachers and parents noted that children were more likely to wash their hands regularly and correctly at school and home. Integrating dance, song, and handwashing movements engaged the children, making the learning process enjoyable and memorable. These results suggest that the Handwashing Dance has considerable potential for broader application in early childhood health education, promoting lifelong healthy habits. However, the study’s limitations, including its small sample size and single-site focus, highlight the need for further research with larger, diverse populations to validate these findings. This study underscores the importance of incorporating interactive and play-based approaches in health education to foster positive health behaviors from an early age. Further research could explore the scalability of this approach and its effectiveness in diverse educational settings.